Associative Nitrogen Fixation in Lowland Rice - Shrestha, Raj K; Maskey, Surya L (Nepal Agriculture Research Journal, 2010)
Nitrogen (N), a most limiting nutrient, is the input required in the largest quantity for lowland rice production. The concerns on N economy and efficiency and its impact on environment have renewed interest in exploring alternative or supplementary N source for sustainable agriculture. Several studies have indicated the existence of significant rice genotypic differences in N2 fixation stimulating traits (NFS). Rice genotypes with high NFS are desirable because they add N to the soil-water-plant system without additional farm inputs and reduce dependence on fertilizer. Large genotypic differences in percent N derived from air (% Ndfa) like 1.5% in Abang Basur, medium maturing genotype, to 21% in Oking Seroni, late maturing genotype, indicates potential of isolating genotypes with high NFS for sustainable agriculture. The exogenous supply of nitrogenous fertilizer to lowland rice significantly inhibited N fixation but improved plant growth. Where as phosphorous fertilizer did not affect atom % 15N excess and % Ndfa significantly but slight decrease in atom % 15N excess and increase in N2 fixation was observed. Inhibitory effect of exogenous supply of N fertilizer indicates limited potential of associative N2 fixation to significantly benefit agriculture. Farmers would have to withhold N fertilizer from their rice crop in order to increase biological N2-fixation associated with rice. If they do such practice the plants will be N deficient and might have a lower yield. However, the development of N fixation in response to a deficiency of available N may well be an integral part of the N cycle of natural ecosystem and low input farming system there by maintaining a N balance in the environment. Key words: Fertilizer; fixation; nitrogen; rice DOI: 10.3126/narj.v6i0.3373 Nepal Agriculture Research Journal Vol.6 2005 pp.110-111